Efektivitas Projek Penguatan Profil Pelajar Pancasila Terhadap Keterampilan Berpikir Tingkat Tinggi Siswa Sekolah Dasar - Pratama, Yoga Adi; Dewi, Laksmi (Jurnal Didaktika Pendidikan Dasar, 2024)
In this complex era, individuals must possess higher-order thinking skills (HOTS).However, many facts indicate that the HOTS of students in Indonesia are low. This study aims to determine the effectiveness of the Projek Penguatan Profil Pelajar Pancasila (P5) on HOTS of elementary school students. A quantitative approach with a one-group pretest-posttest design was employed. The instrument used was a test of higher-order thinking skills, reinforced by formative assessments in the form of P5 rubrics. Purposive sampling was used, with the sample consisting of fifth-grade students from SDN Baros Mandiri 7 for the 2022/2023 academic year. Data analysis was conducted using the T-test. Results showed a significant difference between pretest and posttest scores, with a significance value of 0.001. The average posttest score was 73, categorized as good, while the average pretest score was 32, categorized as poor. Formative assessment scores supported this positive outcome, with all P5 rubric categories being classified as good. This finding shows that the development of HOTS is not only the domain of intracurricular activities, but can also be done through co-curricular activities such as P5. The conclusion of this study is that P5 is effective in improving students' HOTS.